Social work research ethics in China: A scoping review of research involving human subjects during COVID-19 - Wang, Yixuan; Wu, Shiyou; He, Longtao; Li, Linjing; Wang, Zijiao (International social work, 2023)
As the first review to systematically explore the scope and application of Chinese social work research ethics, this study incorporated web-crawling technology in the scoping review process and identified 18 eligible studies from 1168 publications from January 2020 to July 2021. Findings suggest that social work scholars are aware of research ethics when conducting human subjects research in the Chinese population. Yet, many failed to fully demonstrate practical considerations of internationally accepted ethical principles (e.g. respect for persons). We discuss education on research ethics, new challenges of the digital age, and considerations of Chinese culture in developing ethical protocols for social work research in China.